Nanoparticles‐assisted delivery of antiviral‐siRNA as inhalable treatment for human respiratory viruses: A candidate approach against SARS‐COV‐2. Issue 6 (12th October 2020) - Ullah, Ata; Qazi, Javaria; Rahman, Lutfur; Kanaras, Antonios G.; Khan, Waheed S.; Hussain, Irshad; Rehman, Asma
Abstract: The current pandemic of coronavirus disease 2019 (COVID‐19) caused by severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) has challenged healthcare structures across the globe. Although a few therapies are approved by FDA, the search for better treatment options is continuously on rise. Clinical management includes infection prevention and supportive care such as supplemental oxygen and mechanical ventilatory support. Given the urgent nature of the pandemic and the number of companies and researchers developing COVID‐19 related therapies, FDA has created an emergency program to move potential treatments with already approved drugs to patients as quickly as possible in parallel to the development of new drugs that must first pass the clinical trials. In this manuscript, we have reviewed the available literature on the use of sequence‐specific degradation of viral genome using short‐interfering RNA (siRNA) suggesting it as a possible treatment against SARS‐CoV‐2. Delivery of siRNA can be promoted by the use of FDA approved lipids, polymers or lipid‐polymer hybrids. These nanoparticulate systems can be engineered to exhibit increased targetability and formulated as inhalable aerosols. Abstract :